The nutritional value of cow blood meal and its effects on growth performance, haematology and plasma enzymes of hybrid catfish (2002)
The nutritional potential of sun-dried cow blood meal (CBM) was investigated for its effect on growth performance, haematology and plasma enzyme activities in hybrid catfish fingerlings (Clarias gariepinus Male x Heternbrunchus longifilis Female), in an assay that lasted for twelve weeks. Six graded diets containing 0, 5, 10, 15, 20 and 25 percent of CBM were compounded. Ten fingerlings (mean weight 4.23+0.64g) per tank were reared under laboratory conditions in eighteen plastic tanks, each containing 12 liters of water. The fingerlings were fed 3% of their body weight daily, with bimonthly adjustments. At the end of the 84-day experiment, growth performance parameters such as weight gains, specific growth rate (SGR) and feed conversion ratio (FCR) were determined. Blood samples were pooled from each treatment on days 0, 42 and 84 for haematotogical and plasma enzyme analyses. The specific growth rate and the feed conversion ratio were best in the fish fed the control (0% sun-dried CBM) diet and poorest in the fish fed 25% CBM diet inclusion. There were no significant differences (P>0.05) between mean daily weight gains, specific growth rate and feed conversion ratios of fish fed diet 2 (5% CBM) and the control diet. The higher the inclusion level of the sun-dried CBM in the experimental diets, the poorer the nutrient utilization and growth performance. Hematological and pIasma enzyme analyses revealed progressively severe macrocytic normochromic, anaemia, leucocytosis and high enzymatic activities of plasma alanine aminotransferase (ALT) and-aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT) and alkaline phosphatase (ALP) in fish fed increasing levels of sun-dried CBM. These enzymatic changes imply liver, kidney and/or cardiac damage, and opportunistic systemic bacterial infection. It can be inferred that for optimum growth performance, best nutrient utilization and unimpaired haematological and plasma enzyme activities in hybrid Clarias, a 5 % level of sun-dried CBM inclusion in their diet is recommended.